AB0588 INFECTION AGGRAVATED DECREASE OF THE LEVEL OF TH17 AND TREG CELLS AND LOW-DOSE IL-2 REBALANCED TH17/TREG IN THE PERIPHERAL BLOOD OF PATIENTS WITH IDIOPATHIC INFLAMMATORY MYOPATHY. (13th June 2020) - Liang, Y.; Wen, H. Y.; Duan, Y.; Liu, Y.; Yu, Z.; Niu, W.; Gao, C.
Abstract : Background: Idiopathic inflammatory myopathies (IIM) are featured by a series of clinical presentation such as proximal muscle weakness, increased serum levels of creatine kinase and other muscle enzymes and involvement of other organs and systems [1, 2], which results in high morbidity and early mortality [3] . We have known the changes of the level of Th17 and Treg cells in IIM in previous studies [4-6] . However, whether infection affects lymphocyte subsets or not and whether the effect of low-dose interleukin-2 (IL-2) can be influenced by the use of immunosuppressants or not are still unclear. Objectives: The study aimed to explore the changes of lymphocyte subsets in patients of IIM with or without important organ infection, and the restoration of Th17/Treg after receiving low-dose IL-2. Methods: A total of 118 IIM patients were enrolled and classified into infection group and non-infection group based on the important organ infection. Of them, 48 cases were treated with low dose IL-2 (5.0*10 5 IU for 5 days). The absolute number of peripheral total T, B, CD4 + T, CD8 + T, NK, Th1, Th2, Th17 and Treg cell subsets were analyzed by flow cytometry combined with absolute counting beads. Clinical data, laboratory examinations and the levels of peripheral lymphocyte subsets were analyzed retrospectively. Results: In these patients, especially in the infection group, the absolute number of T, CD4 + T, CD8 + T, NK, Th1, Th2, Th17 and Treg cells were significantly decreased as compared with that in the healthy controls, which were significantly increased by low dose IL-2 (especially Treg cells) treatment. The levels of ESR, LDH and HBDH and the ratio of Th17/Treg were significantly lower than those before IL-2 treatment ( Z =-2.237, -2.083, -2.140, -3.663, P =0.025, 0.037, 0.032, 0.000). The 48 cases who received IL-2 treatment were divided into 2 groups according to whether they used immunosuppressants. There was no significant difference in the absolute number of T, B, CD4 + T, CD8 + T, Th1, Th2, Th17 and Treg cells, the proportion of Th17 and Treg cells and the ratio of Th17/Treg between the 2 groups ( P >0.05). Conclusion: Global decrease in lymphocyte subsets was found in IIM patients, especially those who had important organ infection. A significant re-balance of Th17/Treg was observed after receiving treatment with low-dose IL-2. Furthermore, the restoration of lymphocyte subsets showed similar degree after treatment with or without immunosuppressants. Low-dose IL-2 may become a potential therapy for IIM patients. The mechanism of lymphocyte decrease in IIM is required further to study. References: [1]Clark K E N, Isenberg D A. A review of inflammatory idiopathic myopathy focusing on polymyositis[J]. European Journal of Neurology, 2017. [2]Tieu J, Lundberg IE, Limaye V. Idiopathic inflammatory myositis. Best Pract Res Clin Rheumatol. 2016. 30(1): 149-68. [3]Mandel DE, Malemud CJ, Askari AD. Idiopathic Inflammatory Myopathies: A Review of the Classification and Impact of Pathogenesis. Int J Mol Sci. 2017. 18(5). [4]Zhang SX, Wang J, Sun HH, et al. Circulating regulatory T cells were absolutely decreased in dermatomyositis/polymyositis patients and restored by low-dose IL-2. Ann Rheum Dis. 2019 . [5]Espinosa-Ortega F, Gómez-Martin D, Santana-De Anda K, Romo-Tena J, Villaseñor-Ovies P, Alcocer-Varela J. Quantitative T cell subsets profile in peripheral blood from patients with idiopathic inflammatory myopathies: tilting the balance towards proinflammatory and pro-apoptotic subsets. Clin Exp Immunol. 2015. 179(3): 520-8. [6]Feng M, Guo H, Zhang C, et al. Absolute reduction of regulatory T cells and regulatory effect of short-term and low-dose IL-2 in polymyositis or dermatomyositis. Int Immunopharmacol. 2019. 77: 105912. Acknowledgments: Thanks for the support of my teachers, classmates and my family. Disclosure of Interests: None declared